Ответы и объяснения

Лучший Ответ!
2013-06-22T14:28:59+00:00

1)  x^{2} + \frac{2x-3}{2x-3} > 0

 x^{2} > 0, x \neq \frac{3}{2}

Ответ:

 x = R, x \neq 0, x \neq \frac{3}{2}

2)  \frac{x^{2} + 2x - 3}{2x - 3} > 0

 

 \frac{(x - 1)(x + 3)}{2x - 3} > 0

 

Точки смены знака:

 -3; 1; \frac{3}{2}

Распределение знаков:

+, -, +

Ответ:

 (-3; 1) U  ( \frac{3}{2};\infty)

  • ChrisV3
  • почетный грамотей
2013-06-22T14:31:16+00:00

x^2+2x-3=0

D=4+12=16=4^2

x=-2+4/2=2/2=1

x=-2-4/2=-6/2=-3

(x-1)(x+3)=x^2+2x-3

 

2x-3=0

2x=3

x=3/2

(2x-3)=(x-3/2)

 

((x-1)(x+3))/(x-3/2)>0

 

Ответ: (-3;1) и (3/2; + бесконечность).